2019
DOI: 10.1088/1367-2630/ab0118
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear excitations in magnetic lattices with long-range interactions

Abstract: We study-experimentally, theoretically, and numerically-nonlinear excitations in lattices of magnets with long-range interactions. We examine breather solutions, which are spatially localized and periodic in time, in a chain with algebraically-decaying interactions. It was established two decades ago (Flach 1998 Phys. Rev. E 58 R4116) that lattices with long-range interactions can have breather solutions in which the spatial decay of the tails has a crossover from exponential to algebraic decay. In this articl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 55 publications
(103 reference statements)
1
13
0
Order By: Relevance
“…The dashpot γ qm,n is a phenomenological term that we add to account for damping. Using such a term has yielded reasonable agreement with experiments in other, similar lattices [19,36,37]. The quantity F ext m,n is the external force that we apply to the magnet at (m, n).…”
Section: Methodssupporting
confidence: 69%
“…The dashpot γ qm,n is a phenomenological term that we add to account for damping. Using such a term has yielded reasonable agreement with experiments in other, similar lattices [19,36,37]. The quantity F ext m,n is the external force that we apply to the magnet at (m, n).…”
Section: Methodssupporting
confidence: 69%
“…For instance, waves cannot propagate freely through linear phononic crystals in the stop bands. But it was reported that different types of solitary waves, e.g., the KdV-like solitons [18][19][20], gap solitons [21][22][23], and gap breathers [24,25], can propagate in the stop bands through nonlinear phononic crystals. As is well known, a soliton is a solitary wave that can propagate stably with the dynamic behavior like a "particle."…”
Section: Introductionmentioning
confidence: 99%
“…We note the existence of the second and the third harmonic of the excitation frequency in Figure 5B,C, due to the inherent nonlinearity in magnetic lattices. Such nonlinear response can be harnessed by increasing the amplitude of the excitation and introducing defects within the lattice (Boechler et al, 2011;Mehrem et al, 2017;Deng et al, 2018;Molerón et al, 2019;Chong et al, 2020;.…”
Section: Resultsmentioning
confidence: 99%